2021
DOI: 10.3390/ijms22073798
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol and the Canonical WNT/β-Catenin Pathway in Glaucoma

Abstract: Glaucoma is a progressive neurodegenerative disease which constitutes the main frequent cause of irreversible blindness. Recent findings have shown that oxidative stress, inflammation and glutamatergic pathway play key roles in the causes of glaucoma. Recent studies have shown a down regulation of the WNT/β-catenin pathway in glaucoma, associated with overactivation of the GSK-3β signaling. WNT/β-catenin pathway is mainly associated with oxidative stress, inflammation and glutamatergic pathway. Cannabidiol (CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 216 publications
(163 reference statements)
0
15
0
Order By: Relevance
“…THC (via CB1 activation) and CBD were shown to inhibit Akt phosphorylation in colorectal cancer cells and to induce apoptosis in these cells via inhibition of the PI3K-Akt survival signaling cascade ( Figure 1 ; [ 72 , 73 ]). In contrast, CBD and THC were suggested to promote PI3K/Akt signaling and thereby downregulate the expression of GSK3-β, a serine/threonine kinase and an inhibitor of the Wnt/β-catenin pathway in various glaucoma-related models [ 74 ]. However, these trends of upregulation of PI3K/Akt signaling by CBD or THC were primarily shown in non-cancerous cells (e.g., mesenchymal stem cells derived from gingiva; non-cancerous mice brain [ 74 ]) and are opposite to what was reported for cancer cells [ 72 , 73 ].…”
Section: Preclinical Evidence On the Cannabis Mode Of Action On Genet...mentioning
confidence: 99%
“…THC (via CB1 activation) and CBD were shown to inhibit Akt phosphorylation in colorectal cancer cells and to induce apoptosis in these cells via inhibition of the PI3K-Akt survival signaling cascade ( Figure 1 ; [ 72 , 73 ]). In contrast, CBD and THC were suggested to promote PI3K/Akt signaling and thereby downregulate the expression of GSK3-β, a serine/threonine kinase and an inhibitor of the Wnt/β-catenin pathway in various glaucoma-related models [ 74 ]. However, these trends of upregulation of PI3K/Akt signaling by CBD or THC were primarily shown in non-cancerous cells (e.g., mesenchymal stem cells derived from gingiva; non-cancerous mice brain [ 74 ]) and are opposite to what was reported for cancer cells [ 72 , 73 ].…”
Section: Preclinical Evidence On the Cannabis Mode Of Action On Genet...mentioning
confidence: 99%
“…In canonical Wnt/β‐catenin signaling, once Wnt is bound to Wnt ligands, degradation from the Dvl‐Axin‐APC‐GSK3 complex is prevented, and active (nonphosphorylated) β‐catenin is free to translocate to the nucleus and combine with the transcription factors TCF/LEF to initiate the transcription of Wnt target genes. [ 59 ] Our findings suggested that 5‐1 hydrogels may induce and enrich CSCs through Wnt/β‐catenin signaling, which has been considered a critical signaling pathway for CSC self‐renewal. [ 8,60 ]…”
Section: Resultsmentioning
confidence: 97%
“…In vivo activation of cannabinoid receptors in mouse brains resulted in increased GSK3 inhibition [ 131 ]. The antioxidant action of CBD is more likely mediated by NRF2 [ 132 ]. Importantly, promoting NRF2 activity through GSK3 inhibition already showed promising effects in AD [ 133 , 134 , 135 ] and PD [ 136 , 137 ], and therefore pave the way to potential treatments for oxidative stress-related retinal diseases.…”
Section: Gsk3 Involvement In Cellular Functions Deregulated During Re...mentioning
confidence: 99%